Rapid Proteasomal Degradation of Mutant Proteins Is the Primary Mechanism Leading to Tumorigenesis in Patients With MissenseAIPMutations - Laura C. Hernández‐Ramírez; F. Martucci; Rhodri M. L. Morgan; Giampaolo Trivellin; Daniel Tilley; Nancy Ramos-Guajardo; Donato Iacovazzo; Fulvio D’Acquisto; Chrisostomos Prodromou; Márta Korbonits (2016)
The pathogenic effect of mutations in the aryl hydrocarbon receptor interacting protein (AIP) gene (AIPmuts) in pituitary adenomas is incompletely understood. We have identified the primary mechanism of loss of function for missense AIPmuts. This study sought to analyze the mechanism/speed of protein turnover of wild-type and missense AIP variants, correlating protein half-life with clinical parameters. Half-life and protein–protein interaction experiments and cross-sectional analysis of AIPmut positive patients' data were performed in a clinical academic research institution. Data were obtained from our cohort of pituitary adenoma patients and literature-reported cases. Protein turnover of endogenous AIP in two cell lines and fifteen AIP variants overexpressed in HEK293 cells was analyzed via cycloheximide chase and proteasome inhibition. Glutathione-S-transferase pull-down and quantitative mass spectrometry identified proteins involved in AIP degradation; results were confirmed by coimmunoprecipitation and gene knockdown. Relevant clinical data was collected. Half-life of wild-type and mutant AIP proteins and its correlation with clinical parameters. Endogenous AIP half-life was similar in HEK293 and lymphoblastoid cells (43.5 and 32.7 h). AIP variants were divided into stable proteins (median, 77.7 h; interquartile range [IQR], 60.7–92.9 h), and those with short (median, 27 h; IQR, 21.6–28.7 h) or very short (median, 7.7 h; IQR, 5.6–10.5 h) half-life; proteasomal inhibition rescued the rapid degradation of mutant proteins. The experimental half-life significantly correlated with age at diagnosis of acromegaly/gigantism (r = 0.411; P = .002). The FBXO3-containing SKP1–CUL1–F-box protein complex was identified as the E3 ubiquitin-ligase recognizing AIP. AIP is a stable protein, driven to ubiquitination by the SKP1–CUL1–F-box protein complex. Enhanced proteasomal degradation is a novel pathogenic mechanism for AIPmuts, with direct implications for the phenotype. We determined that protein instability, leading to shortened protein half-life, is a novel pathogenic mechanism for mutations in the AIP gene with clinical significance for pituitary adenoma patients.